Political entrenchment and GDP misreporting - Ho Fai Chan; Bruno S. Frey; Ahmed Skali; Benno Torgler (Center for Economic Studies and ifo Institute (CESifo), 2019)
By examining discrepancies between officially reported GDP growth figures and the actual economic growth implied by satellite-based night time light (NTL) density, we investigate whether democracies manipulate officially reported GDP figures, and if so, whether such manipulation pays political dividends. We find that the over-reporting of growth rates does indeed precede increases in popular support, with around a 1% over-statement associated with a 0.5% increase in voter intentions for the incumbent. These results are robust to allowing the elasticity of official GDP statistics to NTL to be country specific, as well as accounting for the quality of governance, and checks and balances on executive power.
Keywords: D72; D73; O43; 330; manipulation; political entrenchment; electoral cycles; trust; popular support; GDP; night lights